Heterologous expression and purification of recombinant human protoporphyrinogen oxidase IX: A comparative study - Zora Novakova (Public Library of Science (PLoS), 2021)
Human protoporphyrinogen oxidase IX (hPPO) is an oxygen-dependent enzyme catalyzing the penultimate step in the heme biosynthesis pathway. Mutations in the enzyme are linked to variegate porphyria, an autosomal dominant metabolic disease. Here we investigated eukaryotic cells as alternative systems for heterologous expression of hPPO, as the use of a traditional bacterial-based system failed to produce several clinically relevant hPPO variants. Using bacterially-produced hPPO, we first analyzed the impact of N-terminal tags and various detergent on hPPO yield, and specific activity. Next, the established protocol was used to compare hPPO constructs heterologously expressed in mammalian HEK293T17 and insect Hi5 cells with prokaryotic overexpression. By attaching various fusion partners at the N- and C-termini of hPPO we also evaluated the influence of the size and positioning of fusion partners on expression levels, specific activity, and intracellular targeting of hPPO fusions in mammalian cells. Overall, our results suggest that while enzymatically active hPPO can be heterologously produced in eukaryotic systems, the limited availability of the intracellular FAD co-factor likely negatively influences yields of a correctly folded protein making thus the E.coli a system of choice for recombinant hPPO overproduction. At the same time, PPO overexpression in eukaryotic cells might be preferrable in cases when the effects of post-translational modifications (absent in bacteria) on target protein functions are studied.